Superior Volumetric Capability Dual‐Ion Batteries Enabled by A Microsize Niobium Tungsten Oxide Anode. (20th March 2022) - Xu, Yongtai; Feng, Jianze; Ma, Hongyun; Zhu, Jiaojiao; Zhang, Xu; Lang, Junwei; Yang, Shengrong; Yan, Xingbin
Abstract: Dual‐ion batteries (DIBs) have gained great attention due to their advantages of high operating voltage and low cost. However, the overall performance of the reported DIBs falls far below expectation. In particular, electrode materials with rapid‐charging kinetics and high volumetric packing densities are still in short supply. Herein, a holistic design of the DIB is proposed by using a Wadsley–Roth phase niobium tungsten oxide as the anode, which possesses facile ion transport tunnels and ultrahigh electrode density to deliver superior volumetric performance (521.5 Ah L −1 at 0.2 C and 154.3 Ah L −1 at 60 C), and choosing graphite as the cathode. Benefiting from the respective advantages of this novel anode and the graphite cathode, the as‐built DIB full cell exhibits high volumetric and excellent rate performance (137.7 Ah L −1 at 1 C and 79.2 Ah L −1 at 5 C), and long‐term cyclic stability (1000 cycles at 5 C with negligible capacity attenuation). More impressively, such cells can deliver a high volumetric energy density (422.7 Wh L −1 ) and power density (8.3 kW L −1 ) . Furthermore, the comprehensive charge storage chemistry of this DIB is elaborated by operando electrochemical characterizations, and this assembly of flexible pouch cells shows its practical prospects. Abstract : A holistic design of the dual‐ion battery configuration is proposed by coupling a Wadsley–Roth phase Nb16 W5 O55 anode material with the low‐cost graphite cathode, which enables superior volumetric performance attributing to intrinsic open tunnel framework and ultrahigh electrode density of Nb16 W5 O55 . In addition, the assembly of the flexible pouch cell demonstrates reliability and practicability.